IMPLEMENTASI MODEL PROBLEM BASED LEARNING BERBANTUAN TES SUPERITEM TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATERI KELARUTAN DAN HASIL KALI KELARUTAN - Nita Risma Yanti; Bambang Suharto; Syahmani Syahmani (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstract. A research on the implementation of problem based learning model aided superitem test of the ability of problem solving solubility and solubility product in SMA Negeri 1 Martapura. The research was quasi experimental design with nonequivalent control group. The study population were students of class XI IPA SMAN 1 Martapura with a sample of 36 students of class XI student of Mathematics 1 and 35 2 XI MIPA obtained by purposive sampling technique. Data were collected with engineering test and non-test and analyzed using t-test and descriptive analysis. The results showed that (1) There are differences in problem solving ability of students to the application of problem based learning model superitem aided test and application of problem based learning model, (2) Activity student on the application of problem based learning model aided superitem tests more active than the student activity on the application Problem Based Learning models and, (3) students give positive response to the application of problem based learning model aided superitem test.Keywords: superitem test, problem based learning, problem solving.